2017
DOI: 10.18632/oncotarget.16313
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of 21-gene recurrence score in 980 Chinese estrogen receptor-positive, HER2-negative early breast cancer patients

Abstract: AimThe current study aimed to explore the distribution patterns of 21-gene recurrence score (RS) assay in Chinese early breast cancer patients.MethodsNine hundred and eighty consecutive estrogen receptor(ER)-positive, human epidermal growth factor receptor 2 (HER2)-negative early breast cancer patients treated at Ruijin Hospital, Shanghai Jiaotong University, School of Medicine from 2009 to 2016 were retrospectively recruited. Reverse transcriptase-polymerase chain reaction (RT-PCR) assay of 21 genes were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 25 publications
4
35
0
Order By: Relevance
“…RS distributed differently according to PR status but the difference did not meet statistical significance, which may be resulted from the insufficient sample size. Moreover, both PR status and Ki-67 index were identified as independent predictors for RS in our previous study in 980 Chinese estrogen receptor-positive, HER2-negative breast cancer patients [15]. Multivariate analyses in our current study showed that molecular subtype defined by Ki-67 and PR level was an independent predictor for RS in both MC and IDC cohorts.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…RS distributed differently according to PR status but the difference did not meet statistical significance, which may be resulted from the insufficient sample size. Moreover, both PR status and Ki-67 index were identified as independent predictors for RS in our previous study in 980 Chinese estrogen receptor-positive, HER2-negative breast cancer patients [15]. Multivariate analyses in our current study showed that molecular subtype defined by Ki-67 and PR level was an independent predictor for RS in both MC and IDC cohorts.…”
Section: Discussionsupporting
confidence: 61%
“…The methods of sample preparation and RS calculation were similar to that previously described [15,16]. Briefly, hematoxylin and eosin-stained slides were reviewed by pathologists to make sure that the paraffin section used for 21-gene RS analysis contained sufficient tumor tissue.…”
Section: Sample Preparation and Rs Calculationmentioning
confidence: 99%
“…Histological grade was evaluated according to Elston and Ellis scoring system (24). The pathology and immunohistochemistry (IHC) staining methods used in the present study were previously described (25). Briefly, IHC staining was performed on 4 ”m slices of formalin-fixed paraffin-embedded (FFPE) tissue sections.…”
Section: Evaluation Of Er Pr Her2mentioning
confidence: 99%
“…The tests were performed on formalin-fixed, paraffin-embedded tissues, as previously described (10,25). In brief, fixed tissues were incubated for 5-10 h in 10% neutral-buffered formalin prior to being alcohol-dehydrated and embedded in paraffin.…”
Section: -Gene Rs Testingmentioning
confidence: 99%
See 1 more Smart Citation